Female, Black, and Able: Representations of Sojourner Truth and Theories of Embodiment - Minister, Meredith (Disability Studies Quarterly, 2012)
Sojourner Truth exists in American popular culture as a strong contributor to the movements for abolition and women’s rights. In order to maintain this image of strength and make the case that black women are just as capable as white men, Truth intentionally elided her disabled right hand. This article explores representations of Sojourner Truth in relation to her nineteenth century context and, in particular, social stigmas regarding race, gender and disability. The interpretations of pictures, a painting, and two events contained in Truth's Narrative suggest that Truth argued against gender and racial oppression by operating with an ideology of ability that suggested that both women and African-Americans are strong, powerful, and able. As Truth maintained an ideology of ability in order to subvert gender and racial hierarchies, she offers a case study into the benefits of intersectional approaches to historical studies. Key Words Sojourner Truth, disability, race, gender, feminism, nineteenth century